The Economically Active Population in Tijuana and that of Mexican Origin in San Diego from 1970 to 2010 - Carolina Pineda Chávez; Roberto Ham Chande (El Colegio de la Frontera Norte, A.C., 2016)
There is a strong cross-border demographic and socioeconomic dynamic between t ijuana and s an Diego; job opportunities in s an Diego have brought it a growing population of mexican origin. These two cities' interrelated economies bring about changes in the popula - tion and economic activity. This article examines the economic context from 1970 to 2010, including key events such as the Border industrialization Program, the simpson- rodino act, the n orth a merican Free t rade a greement, and the 2008 f inancial crisis. t ijuana's main employer is manufacturing, while in s an Diego services and commerce are the main employ - ers for workers of m exican origin, who are increasing their participation in the professional services sector.